The effectiveness of a supplementary reading programme for children in Malaysia’s remote schools - Mohd. Asraf, Ratnawati; Abu Kassim, Noor Lide; Sheikh Ahmad, Ismail; Abdul Rahman, Zainurin (IDOSI Publication, 2013)
Providing access to quality education should be viewed as a social responsibility. And the backbone of a good education system lies in its ability to promote literacy among the community, particularly the children. This paper reports the findings of a study conducted to evaluate the effectiveness of a supplementary reading programme conducted in remote schools in the states of Sabah and Sarawak, Malaysia. Using the qualitative naturalistic framework to programme evaluation proposed by Patton (2001) and Guba and Lincoln (1981, 1992)and using a mixed-method approach comprising quantitative and qualitative data collection and analytictechniques, a questionnaire survey was conducted on 2,734 students and 142 teachers from 40 primary schools in Sabah and Sarawak and triangulated with qualitative data from the interviews of students and teachers as well as observations of their reactions to the programme and reading camps. The results suggest that the supplementary reading programme has improved the students’ attitudes towards reading, motivated them to read extensively and improved their reading habits.